MOTIF PEMBENTUKAN YAYASAN PEDULI KASIH ANAK BERKEBUTUHAN KHUSUS - Tuwankotta, Naomi Pratiwi (Paradigma, 2021)
This research aims to find out the motives of the cause and the goal of the establishment of Yayasan Peduli Kasih that focus on children with special needs. This study is to identify the identity of the founder of the Foundation and Know the goal of the Yayasan Peduli Kasih established. The interesting about this research is the Founder does not have an outstanding educational background but willing to retire early as a doctor and as a lecturer. The method that used for the study is qualitative with a phenomenological approach to Alfred Schutz's perspective which refers to the cause motive and the goal motive. The subjects in this study consisted of four subjects. The process of collecting data with in-depth interviews, the website, and social media of the founder.The results obtained in this study are the motives for the establishment of Yayasan Peduli Kasih, whis is the founder has a high education so that he has a good social networking, Experience attending Seminar in America so he is moved to 2 empower disabilities, collecting 'good charity', feeling the challenges of raising children with disabilities and he has experiences of deterioration in home life then the goal of establishment this Yayasan Peduli Kasih abk is the founder sees that empowering disability is an opportunity to build a broader social network internationally. Keywords: Phenomenological, Children with Special Needs, Yayasan Peduli Kasih that focus on children with special needs.